Advanced Flood Characterization Focused to Optimal City Protection Planning - Hajdari Llapashtica, Venera; Misini, Labeat; Gjorgjiev, Igor; Ivanoski, Dragan; Ristic, Jelena; Ristic, Danilo (Civil Engineering Journal, 2026)
Following the increasing demand for optimal protection of urban areas against natural multi-hazards, we developed an upgraded urban development planning (UUDP) method integrating four principal planning layers along with the initial zero-planning layer and its related sublayers that systematically characterize the potential natural disasters. The significance of pre-planning characterization for natural disasters was demonstrated through a flood disaster case study, which included the flood analysis options of the historic city of Peja. Herein, we systematically review the representative results from a study on the characteristics and magnitudes of flood waves in the Bistrica River generated by storm runoff within the basin, completed using advanced worldwide HEC-HMS software. Consequently, the advanced HEC-RAS analysis software was employed to evaluate the effects of 24-h precipitation events on both the extent and magnitude of flooding. Existing multi-hazard effects were systematically incorporated into planning through the upgraded zero multi-layered method, which involved a detailed characterization of all relevant multi-hazards. The original flood hazard analysis results, including total inundated area (141.5 - 432.8 ha), maximum water depth (4.28 - 5.94 m) and velocity (4.76 - 5.94 m/s), clearly demonstrated tangible improvements in implementing the new UUDP method for optimal urban multi-hazard protection solutions.